OFFSHORIZATION AS A KEY MECHANISM OF SHADOW BUSINESS OPERATIONS - Черницька, Тетяна; Харлов, Володимир (Modern engineering and innovative technologies, 2023)
The article examines the process of offshoring global capital flows as a key mechanism for conducting shadow business operations. The authors reveal the essence and evolution of the concept of "offshore business". An important result of the study is the